The existence of madrasah as the forerunner of the progress of formal educational institutions in the digital and global era - Komariyah, Nining Syamsi; Parwati, Ida; Kurniasih, Asih (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Madrasah has a very important role in nation building. There are two distinct periods in the history of madrasas. The first was the establishment of the Ministerial Decree 3 in 1975 which marked the beginning of the recognition of madrassas as Islamic educational institutions equivalent to general education. The presence of the Three Ministerial Decree is a step in the right direction towards improving school standards. The purpose of this study is to describe the existence of madrasah in formal education in the digital and global era. The method used in this study is descriptive qualitative. The techniques carried out in taking data are direct interviews with school principals, curriculum departments, teachers, administrative and financial taps at MAN 1 Serang City. The results of this research show that MAN 1 Serang City is a madrasah that follows the digital age era, it can be seen from all classes starting from grades ten to twelve learning media have used digital media such as laptops and infocus. In addition, all children are encouraged when KBM to practice directly using computers. However, the obstacle is that not all field teachers can use digital media, due to their limited time and age. In addition, in managing financial tap data, it is currently using digital media in the form of an Institution-Level Financial Application System (SAKTI) which contains planning, implementation and reporting.